"PUBLISH OR PERISH": JAVANESE LANGUAGE MAINTENANCE ON JAVANESE-ENGLISH CODE-SWITCHING SONG - Maharani, Amalina; Sudarwati, Emy (Lire Journal (Journal of Linguistics and Literature), 2021)
This descriptive qualitative study aims to shed new light on Javanese language maintenance through the practice of English-Javanese code-switching reflected in a song entitled Lathi by Weird Genius feat Sara Fajira. The intrinsic merit of the song 'Lathi,' covering cultural values, song lyrics significance, and the song's moral message, were deliberately discussed here. The data are taken from interview transcripts, observation, and documentation. The data were analyzed by first classifying the Lathi song lyrics into types of code switching, investigating the youths’ perception regarding the used of Javanese English code switching in Lathi song, and analyze the aspects of the songs highlighted the idea of Javanese language maintenance. The findings of this study suggest that the phenomenon of code-switching in Lathi songs is deliberately done to keep maintaining Javanese's existence as one of the popular vernacular in Indonesia. Language maintenance of the Javanese language in a song named Lathi can pique the public's interest in learning Javanese by creating Javanese language maintenance represented in its song lyrics. It makes the Javanese language gain popularity in the community, particularly among students and young people. It is, of course, a good sign of minimizing the threat of language shift. The continuous use of the local language as a language maintenance effort will avoid losing the community's first language